Nitric Oxide is Involved in Nitrate-induced Inhibition of Root Elongation in Zea mays - Zhao, D.Y.; Tian, Q.Y.; Li, L.H.; Zhang, W.H.
Background and Aims Root growth and development are closely dependent upon nitrate supply in the growth medium. To unravel the mechanism underlying dependence of root growth on nitrate, an examination was made of whether endogenous nitric oxide (NO)is involved in nitrate-dependent growth of primary roots in maize. + Methods Maize seedlings grown in varying concentrations of nitrate for 7 d were used to evaluate the effects on root elongation of a nitric oxide (NO)donor (sodium nitroprusside, SNP), a NO scavenger (methylene blue, MB), a nitric oxide synthase inhibitor (Nv-nitro-L-arginine, L-NNA), H2O2, indole-3-acetic acid (IAA)and a nitric reducatse inhibitor (tungstate). The effects of these treatments on endogenous NO levels in maize root apical cells were investigated using a NO-specific fluorescent probe, 4, 5-diaminofluorescein diacetate (DAF-2DA)in association with a confocal microscopy. + Key Results Elongation of primary roots was negatively dependent on external concentrations of nitrate, and inhibition by high external nitrate was diminished when roots were treated with SNP and IAA. MB and L-NNA inhibited root elongation of plants grown in low-nitrate solution, but they had no effect on elongation of roots grown in highnitrate solution. Tungstate inhibited root elongation grown in both low- and high-nitrate solutions. Endogenous NO levels in root apices grown in high-nitrate solution were lower than those grown in low-nitrate solution. IAA and SNP markedly enhanced endogenous NO levels in root apices grown in high nitrate, but they had no effect on endogenous NO levels in root apical cells grown in low-nitrate solution. Tungstate induced a greater increase in the endogenous NO levels in root apical cells grown in low-nitrate solution than those grown in high-nitrate solution. Conclusions Inhibition of root elongation in maize by high external nitrate is likely to result from a reduction of nitric oxide synthase-dependent endogenous NO levels in maize root apical cells.
Keywords: NITRATE SUPPLY; NITRIC OXIDE (NO); IAA; ROOT ELONGATION; MAIZE; ZEA MAYS